RANCANG BANGUN FILTER AIR DENGAN FILTRASI SEDERHANA MENGGUNAKAN ENERGI LISTRIK TENAGA SURYA - Meita Rezki Vegatama; Karnila Willard; Riza Hadi Saputra; Ain Sahara; Muhammad Ashar Ramadhan (PETROGAS: Journal of Energy and Technology, 2020)
Water is one of the basic needs in the life of creatures on this earth. Water is used for the body's metabolism, both humans and other living things. Thus, improving water quality is very necessary because it is very influential for the health of humans and other living things. Therefore, the water filter is designed so that this goal is achieved. Not only, water but environmental health is very important. So, this water filter is designed using solar cell technology, which is one of the ideas of renewable energy, and utilizes moringa seeds (moringa oleifera). This water filter is designed using solar panels and batteries as a source of electrical energy. The panel is coupled and will flow energy from the sun. That energy will be absorbed and received by the battery. This water filter uses a coagulation method and also a natural filter that utilizes fibers, silica sand, zeolite stones, and activated carbon. The process of this filter is to compare the input values detected by the sensor, the pH sensor and the turbidity sensor.